1kW 고체산화물 연료전지(SOFC) 시스템 설계 및 자열운전 - 이태희; 최진혁; 박태성; 유영성; 남석우 (한국수소및신에너지학회, 2009)
KEPRI (Korea Electric Power Research Institute) has studied planar type solid oxide fuel cell (SOFC) stacks using anode-supported cells and kW class co-generation systems for residential power generation. In this work, a 1 kW SOFC system consisted of a hot box part, a cold BOP (balance of plant) part, and a hot water reservoir. The hot box part contained a SOFC stack made up of 48 cells, a fuel reformer, a catalytic combustor, and heat exchangers. Thermal management and insulation system were especially designed for self-sustainable operation in that system. A cold BOP part was composed of blowers, pumps, a water trap, and system control units. When the 1 kW SOFC stack was tested using hydrogen at 750℃, the stack power was about 1.2 kWe at 30 A and 1.6 kWe at 50 A. Turning off an electric furnace, the SOFC system was operated using hydrogen and city gas without any external heat source. Under self- sustainable operation conditions, the stack power was about 1.3 kWe with hydrogen and 1.2 kWe with city gas respectively. The system also recuperated heat of about 1.1 kWth by making hot water.